(untitled) (Baghdad Science Journal, 2025)
The present study investigated Haematological changes in Mesopotamichthys sharpeyi, as well as determination genotoxic effects of cadmium chloride on bunni fish by using 120 fingerlings, fish were distributed randomly into four treatments in addition to control group. Fish in first group treated (T1) with cadmium 0.093mg/L with changing water and added cadmium continuously, fish in the second group treated (T2) with cadmium 0.093mg/L with changing water without adding cadmium, third treatment (T3) with cadmium 0.046mg/L with changing water and adding cadmium continuously, and fourth treatment (T4) with cadmium 0.046mg/L with changing water without adding cadmium. Results of blood picture in T1 and T3 showed a significant reduction in red blood cells count, hemoglobin concentration, packed cell volume values, while the number of white blood cells showed a significant increase in its values. Results showed presence of improvement of clinical and microscopical signs and blood picture in T2 and T4, were changed water aquarium continuously and added cadmium only once compared withT1 and T3. Results of the present study concluded that changing water aquarium in the treatments without adding cadmium led to improvement of health status of fish which increased with the passage of time results of blood picture were almost the same of the control group. It could be concluded from the current study that the adding of cadmium to water aquarium containing bunni fish led to decrease in red blood cells count, hemoglobin and packed cell volume values and increase in micronuclei number.